The Dynamics of Power and Prosperity: An Interdisciplinary Study of Saint Pilgrimage in Indonesia - Rohwati, Siti; Hamdani (KARSA Journal of Social and Islamic Culture, 2025)
This research examines the complexity of the relationship between spiritual and economic aspects in the context of the pilgrimage of saints in Indonesia. Using qualitative and anthropological approaches, this research relies on secondary sources of relevant literature. The ’ziarah wali’ (saint pilgrimage), which has strong roots in traditional Muslim cultures, has undergone significant transformations along with economic and political developments in the modern era. This study analyzes how the veneration of holy men in many parts of Javanese culture transformed from religious ritual into social and economic activity manifested in popular tourism. The literature review includes various sources of literature data related to the study of the history of the pilgrimage of saints, socio-cultural changes, government policies related to religious tourism, and the economic impact on the community around the pilgrimage site. The main findings indicate an ongoing negotiation between spiritual values and economic interests in shaping the contemporary pilgrimage landscape in Indonesia. The analysis shows the complex dynamics between pilgrims’ spiritual motivations, local communities' economic interests, and government policies in developing the religious tourism sector. This research contributes to a more nuanced understanding of socioeconomic dynamics in spiritual practices and the implications for policies on cultural heritage preservation and religious tourism development in Indonesia.